Terror [videorecording] the new world war - Lattanzi, Bill.; Westin, AV. ([S.l.] ABC News, 1989)
Documents wars in Beirut, London and Paris portraying terroristic activities.
VHS.
Narrator, Peter Thomas.
Keywords: Terrorism -- Beirut; Bombings -- Beirut; Bombings -- London; Bombings -- Paris; Terrorism -- London; Terrorism -- Paris